Omolabus Jekel in north and central America (Coleoptera: Attelabidae) - Hamilton, Robert W. (Zootaxa, 2005)
The genus Omolabus Jekel is redefined and the genus Xestolabus Jekel is assigned to subgeneric status, New Status, under Omolabus. Fourteen species are recognized in the genus Omolabus in North and Central America: O. angulipennis (Sharp) New Combination, O. callosus (Sharp), O. conicollis (Sharp) New Combination, O. corvinus (Gyllenhal) New Combination, O. fasciventris New Species, O. heterocerus (Sharp) New Combination, O. laesicollis (Gyllenhal) New Combi-nation, O. ligulatus (Sharp), O. longiclava (Sharp) New Combination, O. megalomus New Spe- cies, O. quadratus (Sharp), O. sedatus (Sharp) New Combination, O. spinipectus New Species and O. veracruensis New Species. The following species are placed in New Synonymy: X. constrictipennis (Chittenden), X. tabascoensis Voss, O. brevicollis Sharp and O. biimpressus Voss. Lecto- types are designated for the following Sharp species: O. callosus, O. conicollis, O. heterocerus, O. ligulatus, O. quadratus, and O. sedatus. Identification keys based on external characteristics are provided for the New World genus group Attelabina and for all known Omolabus species occurring in North and Central America. Digital habitus images, illustrations of male genitalia and host plant associations are also included.